2015
DOI: 10.1371/journal.pone.0140928
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Rice Expressing Ictb and FBP/Sbpase Derived from Cyanobacteria Exhibits Enhanced Photosynthesis and Mesophyll Conductance to CO2

Abstract: To find a way to promote the rate of carbon flux and further improve the photosynthetic rate in rice, two CO2-transporting and fixing relevant genes, Ictb and FBP/Sbpase, which were derived from cyanobacteria with the 35SCaMV promotor in the respective constructs, were transformed into rice. Three homologous transgenic groups with Ictb, FBP/Sbpase and the two genes combined were constructed in parallel, and the functional effects of these two genes were investigated by physiological, biochemical and leaf anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 87 publications
5
40
1
Order By: Relevance
“…Additionally, in field studies we demonstrate that plants with simultaneous stimulation of electron transport and of RuBP regeneration had increased iWUE with an increase in biomass.Under glasshouse conditions, increases in photosynthesis were observed in all of the transgenic plants analysed here and these were found to be consistently correlated with increases in biomass. Although increases in photosynthesis and biomass have been reported for plants with stimulation of RuBP regeneration in both model2,3,6,7,34 and crop26,24 species; and electron transport in Arabidopsis and tobacco[28][29][30] , the data presented here provides the first report of increased photosynthesis and biomass by the simultaneous stimulation of electron transport and RuBP regeneration. Increases in A were observed under glasshouse conditions in the leaves of all of the different transgenic tobacco plants and in both of the tobacco cultivars (cv.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Additionally, in field studies we demonstrate that plants with simultaneous stimulation of electron transport and of RuBP regeneration had increased iWUE with an increase in biomass.Under glasshouse conditions, increases in photosynthesis were observed in all of the transgenic plants analysed here and these were found to be consistently correlated with increases in biomass. Although increases in photosynthesis and biomass have been reported for plants with stimulation of RuBP regeneration in both model2,3,6,7,34 and crop26,24 species; and electron transport in Arabidopsis and tobacco[28][29][30] , the data presented here provides the first report of increased photosynthesis and biomass by the simultaneous stimulation of electron transport and RuBP regeneration. Increases in A were observed under glasshouse conditions in the leaves of all of the different transgenic tobacco plants and in both of the tobacco cultivars (cv.…”
mentioning
confidence: 57%
“…Previous research has shown that taking a multi-gene approach to increase the levels of more than one enzyme or protein simultaneously can result in a cumulative increase in photosynthesis and biomass yield 6,7,34 . Building on this approach, the work in this paper aims to test the hypothesis that combining an increase in the activity of a CB cycle enzyme, specifically enhancing RuBP regeneration, together with stimulation of the electron transport chain can boost photosynthesis and yield above that observed when these processes are targeted individually.…”
Section: Introductionmentioning
confidence: 99%
“…However, they could barely survive at ambient levels of atmospheric CO 2 thus showing that other components of the cyanobacterial CCM were necessary for efficient CO 2 fixation in C 3 plants. In contrast, transfer of the cyanobacterial inorganic carbon transporter B (IctB) enhanced biomass accumulation in a variety of plant species, including A. thaliana , tobacco, rice, and soybean . Transfer of the C. reinhardtii putative inorganic carbon transporters LCIA and HLA3 as GFP fusions into A. thaliana resulted in growth comparable with that of wild‐type plants …”
Section: Discussionmentioning
confidence: 99%
“…Here, photosynthetic performance was also increased. However, of the three parameters determining grain yield in rice, i.e., tiller number, filled grains per panicle and grain weight, only tiller number was increased in the double transformant (Gong et al, 2015).…”
Section: Carbon Allocation Between Source and Sinkmentioning
confidence: 93%